Avaliação da qualidade da imagem e da Dose Glandular Média em Mamografia Digital. (Brazilian Journal of Radiation Sciences, 2015)
The most important reference for breast cancer diagnosis is still the mammography. Mammographic technology has evolved in such a way that we have digital systems nowadays. Thus, image generation quality control must evolve as well. In this work, we have evaluated digital image quality and entrance skin dose (ESD) for different breast thicknesses simulated by PMMA plates (one, two, three and four centimeters) for different target filter combinations, suggesting a protocol optimization to the mammographic automatic system.We have used CDMAM 3.4 phantom (a contrast detail phantom) and its software in order to analyze digital images from a Siemens Mammomat Inspiration mammographic equipment. It has been used three combinations of target-filter: Molybdenum Molybdenum, Molybdenum Rhodium, Tungsten Rhodium. Different peak tensions were tested to each configuration: 24 kVp, 26 kVp, 28 kVp and 30 kVp. Altogether 52 different configurations were tested. In order to measure ESD, we used Radcal’s 10x5–6M ionization chamber.Results show that automatic configuration does not offer an optimized process. Tungsten Rhodium was the best option for all breast thicknesses, once it offered the best relation between image quality and mean glandular dose. This result differs from literature which states that the Molybdenum Molybdenum combination is the best option for thin breasts.